Holistic face processing is penetrable … depending on the composite design - Ventura, Paulo (2019)
Holistic processing (HP) of faces is usually measured by the composite effect. While Weston and Perfect [2005. Effects of processing bias on the recognition of composite face halves. Psychonomic Bulletin & Review, 12, 1038–1042. doi:10.3758/BF03206440] found that priming at the local level speeded recognition of components of faces, Gao et al. [2011. Priming global and local processing of composite faces: Revisiting the processing-bias effect on face perception. Attention Perception & Psychophysics, 73, 1477–1486. doi:10.3758/s13414-011-0109-7] found that only global priming had an effect on HP of faces. The two studies used different versions of the composite task (the partial design, which is considered to be prone on bias, and the complete design). However, the two studies also differed in other respects and it is difficult to know to what extent issues with the partial design contributed to the differing conclusions. In the present study, the HP indexed by the complete design measure was augmented by global priming. In contrast, no effect was observed in the partial design index. We claim that the partial design index reflects other factors besides HP, including response bias, and conclude that HP can be understood within the context of domain-general attentional processes.